Four-armed Ganesha - Temples of India Project Team (Jio Institute, 2024)
A four-armed Ganesha, once adorning the temple wall on the Harsha Hill is now housed in the Government Museum, Sikar It is depicted holding an axe and a mala in his lower two hands. The upper two hands carry a bowl of sweets and possibly a flower.